Political Efficacy, Police Legitimacy, and Public Support for Counterterrorism Measures in China - Sun, Ivan Y. (Terrorism and political violence, 2022)
The threat of terrorism has surfaced as a top priority in national and global security over the past two decades. Drawing upon survey data collected by the Chinese General Social Survey, this study assesses the relationships among political efficacy, police legitimacy, and public support for counterterrorism measures in China. The majority of surveyed Chinese people do not favor aggressive law enforcement actions even when a terrorist attack is imminent. Public support for different forms of antiterrorism means is inversely related to the level of coercion associated with each measure, with wiretapping receiving the highest support, followed by stop and search, and detention. Path analysis results showed that self-rated political knowledge lowers people’s positive evaluations of police legitimacy, whereas political influence strengthens such perception. Stronger senses of police legitimacy then lead to lower support for counterterrorism measures. Additionally, females and racial/ethnic minorities are less likely to favor aggressive antiterrorism activities, while older and college-educated people are more inclined to endorse counterterrorism measures. Implications for future research are discussed.